Diapause decision in the small tortoiseshell butterfly, Aglais urticae. Issue 5 (3rd April 2019) - Wiklund, Christer; Lehmann, Philipp; Friberg, Magne
Abstract: Insects in temperate areas spend the inhospitable winter conditions in a resting stage known as diapause. In species that diapause in the larval or pupal stage, the decision whether to diapause or develop directly is customarily taken during the late instars, with long days (i.e., long light phases) and high temperatures promoting direct development. Among butterflies that overwinter as adults, data are rare and variable, but imply that the larval daylength conditions can affect the pathway decision. We studied the small tortoiseshell, Aglais urticae L. (Lepidoptera: Nymphalidae, Nymphalini), which is partially bivoltine from Central Scandinavia and southwards, and tested whether the pathway decision is taken in the larval or adult stage. We reared larvae under long‐day (L22:D2) or short‐day (L12:D12) photoperiods, and recorded the pathway taken by the eclosing adults by scoring their propensity to mate and produce eggs. We also tested whether the larval photoperiod influenced adult ability to diapause by assessing adult survival. The results clearly indicate that (1) there is no detectable effect of larval photoperiod treatment on the pathway decision taken by adults whether to enter diapause or to develop directly, (2) some individuals are obligately univoltine and insensitive to photoperiod during adulthood, whereas (3) other individuals can facultatively enter diapause or direct development, depending on the photoperiod experienced after adult eclosion. Abstract : Insects with two or more generations per year typically decide whether to overwinter or develop directly without diapause, using daylight and temperature as cues. This decision is almost always made during the larval stages – also in species that overwinter as adults. We demonstrate that in Aglais urticae (Lepidoptera: Nymphalidae), the pathway decision is made in the adult stage. This is the first demonstration of the pathway decision being made in the adult stage in a butterfly that overwinters as adult.